1970
DOI: 10.1111/j.1476-5381.1970.tb12897.x
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacological analysis of the peristaltic reflex in the isolated colon of the guinea‐pig or cat

Abstract: Summary1. The peristaltic reflex in the colon was elicited by a localized intraluminal stimulus. The contractile response of the longitudinal coat, which consists of two phases, begins before the start of propulsion. Although the contractions of the longitudinal and circular musculature are usually associated, they may be independent of each other. In particular, the longitudinal contraction does not seem to be necessary for propulsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
68
4
5

Year Published

1974
1974
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 23 publications
2
68
4
5
Order By: Relevance
“…colon motility; enteric neurons; spatiotemporal maps; peristalsis COLONIC MOTILITY IS CONTROLLED by complex interactive processes in the gut, involving both nerve cells (neurogenic) and spontaneous muscle activity (myogenic). A number of studies have characterized fundamental mechanisms in the colon of the guinea pig, mouse, and rabbit and have shown that propagating contractions underlying peristalsis, or other propulsive motor patterns, require activity in the enteric nervous system (8,11,13,14,17,25).…”
mentioning
confidence: 99%
“…colon motility; enteric neurons; spatiotemporal maps; peristalsis COLONIC MOTILITY IS CONTROLLED by complex interactive processes in the gut, involving both nerve cells (neurogenic) and spontaneous muscle activity (myogenic). A number of studies have characterized fundamental mechanisms in the colon of the guinea pig, mouse, and rabbit and have shown that propagating contractions underlying peristalsis, or other propulsive motor patterns, require activity in the enteric nervous system (8,11,13,14,17,25).…”
mentioning
confidence: 99%
“…29,36,49 In contrast, others demonstrated that nicotinic receptors are not essential in mediating peristalsis of the guinea pig distal colon. 50,51 They showed that hexamethonium temporarily arrested peristalsis and fecal pellet propulsion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PN stimulation enhances colonic peristalsis in response to balloon distension while sympathetic stimulation inhibits colonic peristalsis of the guinea pig distal colon in vitro. 36,37 However, it remains unclear whether PN stimulation affects fecal pellet propulsion or luminal pressure changes. As shown in Supplementary Video 2, we have clearly demonstrated that PN stimulation accelerates pellet propulsion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations